Metacognitive strategies and critical thinking in elevating EFL argumentative writing proficiency: Practical insights - Noldy Pelenkahu; Muhammad Ilham Ali; Devilito Prasetyo Tatipang; Ceisy Nita Wuntu; Olga Anneke Rorintulus (Universitas Syiah Kuala, 2024)
This study utilized Kemmis et al.s (2014) action research paradigm. It implemented a two-cycle action study within a single semester, encompassing four stages of learning tasks: comprehension of the problem, monitoring of students learning activities, problem-solving, assessment, and concluding. Every cycle offered learning activities that focused on metacognitive and critical thinking to refine students ability to write persuasive arguments. During the previous cycle, the students showed strong skills in stating their goals and identifying their planned actions. They used different approaches to pinpoint a key topic for their writing and monitor their progress by effectively managing their available time. The investigation found that integrating metacognitive and crucial thinking processes into instructional methods improved students argumentative writing skills, starting with critical skill requirements. Integrating metacognition into writing training is vital for enhancing writing skills at the college level. This study made a special effort to guarantee that each stage was attentively examined and received constructive recommendations for enhancement before going to further steps. However, it is important to acknowledge limitations. The study did not assess the long-term retention of enhanced writing skills, and the sample size may limit generalization. Additionally, while metacognition and critical thinking were beneficial, other factors influencing writing skills were not extensively explored. Future research could address these aspects for a more comprehensive understanding of sustained skill development.